Analysis of the anelastic deformation of high-entropy Pd20Pt20Cu20Ni20P20 metallic glass under stress relaxation and recovery. (30th April 2022) - Duan, Y.J.; Zhang, L.T.; Wada, T.; Kato, H.; Pineda, E.; Crespo, D.; Pelletier, J.M.; Qiao, J.C.
Research highlights: 1 Mechanical response of Pd20 Pt20 Cu20 Ni20 P20 high-entropy metallic glass is revealed and characterized through the stress relaxation and recovery process. 2 Stress relaxation during consecutive strain steps can be well described by the Kohlrausch-Williams-Watts (KWW) function. 3 A constitutive model is also applied to analyze in detail the hierarchy of structural and dynamic heterogeneity. Abstract: The anelastic deformation behavior of Pd20 Pt20 Cu20 Ni20 P20 high-entropy metallic glass was probed by monitoring the stress relaxation and recovery processes. The stress relaxation under consecutive strain steps can be described by the Kohlrausch-Williams-Watts (KWW) function. In addition, considering a hierarchy of relaxation processes related to the structural heterogeneity, a constitutive model is proposed in order to describe the whole process of stress relaxation and determine the contribution of different time scales. Moreover, a crossover from stochastic activation to percolation of flow defects with the ultimate strain can be observed during stress relaxation process. The anelastic recovery process after a strain step is studied as a function of the initial strain level and characterized by means of a direct spectrum analysis. The peaks in the recovery time-spectra revealed the evolution of flow defects in Pd20 Pt20 Cu20 Ni20 P20 high-entropy metallic glass. The understanding of the atomic free-volume zones effect and the anelastic deformation provides important insight into how atomic structural features affect the deformation behavior of high-entropy metallic glasses, and may provide a new avenue into the improvement of their mechanical properties. Graphical abstract: Image, graphical abstract